2018
DOI: 10.5041/rmmj.10316
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Surgical Apgar Score in Predicting Immediate and Late Postoperative Morbidity and Mortality: A Narrative Review

Abstract: Surgical Apgar Score is a simple, 10-point scoring system in which a low score reliably identifies those patients at risk for adverse perioperative outcomes. Surgical techniques and anesthesia management should be directed in such a way that the Surgical Apgar Score remains higher to avoid postoperative morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 53 publications
1
20
0
1
Order By: Relevance
“…In our case series, only the SAS turned to be an independent risk factor. Our results are consistent with those obtained by other authors and summarized in the review on the SAS by Nair et al published in 2017 [ 5 ]. Twenty out of 25 retrospective and 9 out of 11 prospective studies confirmed that the SAS correlated with postoperative morbidity and mortality.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In our case series, only the SAS turned to be an independent risk factor. Our results are consistent with those obtained by other authors and summarized in the review on the SAS by Nair et al published in 2017 [ 5 ]. Twenty out of 25 retrospective and 9 out of 11 prospective studies confirmed that the SAS correlated with postoperative morbidity and mortality.…”
Section: Discussionsupporting
confidence: 94%
“…Twenty out of 25 retrospective and 9 out of 11 prospective studies confirmed that the SAS correlated with postoperative morbidity and mortality. The cut-offs were different between the studies but most of the authors used 6/7 points to differentiate between low- and high-risk patients [ 5 ]. However, to the best of our knowledge, this is the first study reporting on the SAS in frail older patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…four to sevenfold increase in postoperative complications compared to ASA ≤ 2 [25]. Nair et al [22] also noted that the SAS could predict either alone, or in combination with other risk factors, the occurrence of postoperative complications. Therefore, the combination of the SAS and the patient's preoperative physical status may be an ideal model to predict postoperative complications.…”
Section: Resultsmentioning
confidence: 99%
“…Anesthesiologists should also keep in mind that the careful management of intraoperative blood pressure may lead to improved postoperative patients' outcomes. It has been reported that the SAS was not correlated with the postoperative outcomes in orthopedic surgeries performed under regional anesthesia [6,17,22]. Nair et al [22] noted that the initial hypotension that occurred after the administration of a spinal anesthetic was associated with the poor SAS correlation with postoperative complications.…”
Section: Resultsmentioning
confidence: 99%